Optimum Currency Area in Europe: An Alternative Evaluation - KIM, Yoonbai (Institutional Knowledge at Singapore Management University, 2003)
In this paper we explore an alternative scheme to assess the suitability of adopting a common currency by Western European countries. It is based on the role of common regional shocks in the determination of output. The results show that the OCA theory well explains and predicts participation decisions in EMU. We also find that our OCA index is highly consistent with two popular schemes that have been introduced by Bayoumi and Eichengreen.